Controllable frequency and polarization THz filter based on graphene fish‐scale metamaterial. Issue 12 (22nd September 2017) - Dmitriev, Victor; Nascimento, Clerisson; Lima, Roberto; Prosvirnin, Sergey L.
Abstract: In this work, we propose and numerically analyze a new electromagnetic polarization filter in THz region based on graphene fish‐scale structure. The array is composed by graphene strips placed on a metallized dielectric substrate. The filter can operate in two different frequency regions that can be shifted in frequency by appropriate choice of width of the graphene ribbons. We present as an example, at f 1  = 0.483 THz, the structure possesses the reflection coefficient of −0.38 dB for the incident waves with x ‐polarization and −48.05dB for the y ‐polarized ones, while at f 2  = 0.792 THz, the reflection coefficients are −47.25 dB for x ‐polarization and −0.86 dB for y ‐polarization. The physics of the device is based on surface plasmon polariton (SPP) resonances in the graphene. The central frequency can be dynamically adjusted by changing the chemical potential (ie, by an external voltage for example) of the graphene strips.